Graphene type flame-retardant, light-resistant, wear-resistant water-based polyurethane coating
Patent Information
- Application Number
- CN202411657909.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-14
AI Technical Summary
[0013]本发明所要解决的技术问题是紫外吸收剂与聚氨酯涂料共混性差,耐光性级别不高,且聚氨酯阻燃性差,首次将动态可逆过程引入到聚氨酯中,用于解决聚氨酯的耐黄变问题,并协同羟丙基炔丙基醚、香豆素衍生物共同发挥作用,提高聚氨酯耐光性;采用阻燃体系中引入有机硅化合物,增加受热Si-C炭层致密性,将该氮磷硅阻燃剂引聚氨酯链段中,降低聚氨酯燃烧的熔滴性和燃烧的烟雾
[0036](5)传统的无机钼化合物聚氨酯相容性差,分散于聚氨酯体系中放置不到2h就会沉淀,选择1-溴十四烷与N-甲基二乙醇胺进行反应,形成带有羟基的季铵盐化合物,再利用乙酰丙酮钼与该季铵盐化合物发生络合反应,将该钼类化合物引入到该体系,形成能与聚氨酯相容性的有机钼化合物,降低聚氨酯燃烧的烟雾释放量;
Smart Images

Figure CN119371890B_ABST
Abstract
Description
[0001] This invention is a divisional of 202411288162X. Technical Field
[0002] This invention relates to a method for preparing waterborne polyurethane coatings, and particularly to key materials used in graphene-based flame-retardant, light-resistant, and abrasion-resistant waterborne polyurethane coatings. Background Technology
[0003] Polyurethane is one of the six most important synthetic materials. It has great application value in coatings, rubber, foam plastics, fibers, adhesives, synthetic leather and functional polymers. It has become the new polymer material with the most varieties, the widest range of uses and the fastest development.
[0004] Waterborne polyurethane (WPU) is a widely used environmentally friendly polymer produced by the polyaddition reaction of diisocyanate and polyol. WPU possesses advantages such as high mechanical strength, good flexibility, solvent resistance, and corrosion resistance. Therefore, WPU is widely used in the textile industry, wood processing, leather finishing, and automotive industry. However, during use, prolonged exposure to ultraviolet rays from sunlight causes the film surface to yellow, affecting product lifespan. Furthermore, polyurethane has a limiting oxygen index (LOI) of only 20.1%, resulting in rapid combustion and the formation of molten droplets after combustion, causing secondary hazards. Additionally, when used as a coating material, waterborne polyurethane is often subjected to friction, impact, and bending, leading to scratches, microcracks, and other physical damage, resulting in coating destruction, functional loss, and shortened lifespan. These drawbacks severely limit the industrial application of WPU. Therefore, it is necessary to modify it to improve its flame retardancy, light resistance, and abrasion resistance.
[0005] Improving the flame retardancy and light resistance of waterborne polyurethane generally involves chemical and physical modification methods. Chemical modification is a complex process but yields good results, while physical modification is a simple process but less effective.
[0006] Invention patent 2023111285422 employs a hyperbranched flame retardant as a chain extender for the polyurethane synthetic prepolymer in a reaction vessel, and simultaneously uses butyl glycoside (alkyl glycoside) as a chain extender to incorporate a penetrating anionic nonionic emulsifier into the polyurethane chain segments. Saturated sodium bisulfite and urethane are used to synergistically treat the acetone solvent in the polyurethane, as acetone is a major source of VOCs in polyurethane. Furthermore, tannin from Vitex negundo bark is reacted with phosphorus trichloride. Because Vitex negundo bark has a large number of phenolic hydroxyl groups, it reacts with P-Cl, making the resulting Vitex negundo bark easier to char in phosphorus compounds and increasing the charring amount. Ethanolamine is then introduced to increase the hydroxyl content in the system, thereby increasing the carbon content of the charring agent and improving the flame retardancy of the system. The invention has the advantages of not producing molten droplets during combustion, having a yellowing resistance rating of 3.5, and having a low maximum heat release during the combustion of polyurethane materials. However, the invention has a low yellowing resistance rating and a high maximum heat release during combustion. It also does not involve abrasion resistance research, and the bark of Vitex negundo has poor dispersibility in polyurethane, so there is still room for improvement.
[0007] Invention patent 202311129132X describes the design and preparation of a hyperbranched nitrogen-phosphorus-silicon flame retardant for flame retardant treatment of polyurethane. This addresses the flammability defects of polyurethane, as well as the problems of excessive molten droplets and smoke during combustion. It provides a new flame retardant option for polyurethane flame modification. The invention employs a combination of disulfide bonds, coumarin derivatives (photorepair), and multiple dynamic hydrogen bonds, utilizing spiropyran compounds for light absorption and energy release. This allows the coumarin derivatives (photorepair) and disulfide bonds to improve the self-healing durability of polyurethane at room temperature. However, the limitations include the high cost of spiropyran compounds, which increases product costs, and the lack of improvement in abrasion resistance. Furthermore, the pkHHR and THR still require improvement, and the efficiency of the prepared coumarin derivatives still has room for further improvement.
[0008] Regarding the lightfastness of polyurethane, some research has also employed physical blending.
[0009] He Qiuju et al. mixed nano-SiO2 with MDI aromatic isocyanate using a physical blending method. When 0.23% SiO2 was added, the resulting polyurethane emulsion exhibited low UV transmittance. Nano-silica has a strong absorption capacity for ultraviolet light and a strong reflective effect for infrared light. Furthermore, the insufficient coordination on the surface of nano-SiO2 results in strong activity, allowing it to adsorb certain pigment particles and reduce pigment fading caused by ultraviolet irradiation. In addition, during film formation, nano-silica can form a network structure, significantly improving the coating's aging resistance and corrosion resistance. Adding it to the raw materials can improve the polyurethane's resistance to yellowing. Because nano-titanium dioxide has a large specific surface area, it can diffusely reflect some of the ultraviolet light entering the polyurethane material and absorb most of the ultraviolet energy through electron hopping, releasing it in the form of vibrational heat, electron-hole coupling fluorescence, etc. However, the resulting polyurethane solution has poor stability; therefore, chemical modification is necessary.
[0010] Regarding the flame retardancy of polyurethane, some research has also employed physical blending.
[0011] Lü Peng et al. mixed nano-silica with waterborne polyurethane emulsion and found that the nano-silica sol and waterborne polyurethane had good compatibility. When the silica sol content was less than 20%, it did not affect the appearance of the polyurethane emulsion, and its static and dynamic settling rates remained unchanged or showed extremely small changes. Through experiments, it was found that with the increase of nano-silica sol content, the curing time of the coating gradually increased, the hardness initially increased and then tended to stabilize, the tensile strength of the coating initially increased and then decreased, and the elongation at break gradually decreased. The oxygen index increased from the initial 18% to 26.5%, indicating that the nano-silica sol improved the flammability rating of the waterborne polyurethane coating. However, this method has the drawback of poor stability of waterborne polyurethane and did not study the polyurethane droplets and smoke.
[0012] Current research on the flame retardancy and light resistance of waterborne polyurethane coatings reveals shortcomings such as insufficient light resistance and the generation of molten droplets and smoke during combustion. Further improvements are needed to enhance the light resistance and flame retardancy of polyurethane and meet the needs of social development. Summary of the Invention
[0013] The technical problem to be solved by this invention is that the UV absorber has poor compatibility with polyurethane coatings, resulting in low lightfastness and poor flame retardancy of polyurethane. For the first time, a dynamic reversible process is introduced into polyurethane to solve the problem of yellowing of polyurethane. It works synergistically with hydroxypropyl propargyl ether and coumarin derivatives to improve the lightfastness of polyurethane. The invention also introduces organosilicon compounds into the flame retardant system to increase the density of the heated Si-C char layer. This nitrogen-phosphorus-silicon flame retardant is introduced into the polyurethane chain segment to reduce the dripping and smoke during polyurethane combustion.
[0014] Preparation method of graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coatings.
[0015] (1) Prepolymerization: First, vacuum dry the polyol for 18-24 hours; then add 20-25 parts of polyol and 49-64 parts of isocyanate to a flask with a thermometer, glass stopper, stirrer and nitrogen tube inserted, add 0.1-0.3 parts of dibutyltin dilaurate, heat to 80-85℃, rotate at 200-250 r / min, and react for 1-2 hours; adjust the temperature to 75-80℃, add 10-12 parts of polyethylene glycol with a molecular weight of 2000 g / mol to the system and react for 1-2 hours to obtain the prepolymer;
[0016] (2) First chain extension and introduction of disulfide bonds: 2-3 parts of 1,4-butanediol BDO and 2-3 parts of disulfide compound are added to the prepolymer and reacted at 70-80℃ for 1-2 hours. Then, 5-6 parts of polyethylene glycol monomethyl ether (MPEG) are added to the reaction system and reacted at 70℃ for 1-2 hours. During this period, the state of the reactants is constantly observed. If the viscosity increases, acetone is added in small amounts several times to reduce the viscosity. Then, 3-5 parts of ultraviolet absorber, 0.6-1.5 parts of coumarin derivative, 0.3-1.2 parts of hydroxypropyl propargyl ether, 3-5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid are added and reacted at 70-80℃ for 1-1.5 hours.
[0017] (3) Secondary chain extension: Adjust the rotation speed to 250-300 r / min, add 1-2 parts of ethylenediamine, stir and react at 60-70℃ for 0.5-1 h, add 100-120 parts of water, keep the stirring speed at 2000 r / min at 60-70℃, and react for 0.5-1 h to obtain graphene-type flame retardant, light resistant, and wear resistant water-based polyurethane coating;
[0018] The preparation method of nitrogen-phosphorus-silicon flame retardant is as follows: Using 100 mL of tetrahydrofuran as solvent, add 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 3.9–6.5 g of organomolybdenum compound, 0.6–1 g of graphene graft, and 0.5–0.7 g of azobisisobutyronitrile to a four-necked flask. React at 50–60 °C for 1–2 h. Then add 0.1–0.12 mol of maleic anhydride (MA) to the four-necked flask and stir the reaction at 40–50 °C for 4–6 h. Dry in a vacuum oven to obtain the DOPO-MA reaction system. Then add 0.12–0.12 mol of maleic anhydride (MA) to the reaction system. 0.14 mol of diisopropanolamine (DIPA) and 0.41–0.43 g of p-toluenesulfonic acid (TsOH) were placed in a flask, and 50 mL of toluene was added. The mixture was heated at 90–100 °C for 3–6 h, and then dried under vacuum at 85 °C to constant weight to obtain an intermediate flame retardant. 0.01–0.015 mol of tris(1-chloro-2-propyl) phosphate was then added to the intermediate flame retardant, and the pH was adjusted to 7.5. The mixture was reacted at 75–85 °C for 1–2 h, and then the pH was adjusted again to 7.5. 0.01–0.015 mol of methyltrichlorosilane was added, and the mixture was reacted at 80–85 °C for 1–2 h. The mixture was then dried under vacuum to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0019] The polyols are polytetrahydrofuran ether diol and polypropylene glycol, wherein the molecular weight of polytetrahydrofuran ether diol is 1000 g / mol and the molecular weight of polypropylene glycol is 2000 g / mol.
[0020] The isocyanate is either HDI or MDI;
[0021] The disulfide compound is either 2,2'-dithiodiethanol or 2,2-diaminodiphenyl disulfide;
[0022] The ultraviolet absorber is either UV-320 or UV-531.
[0023] The preparation method of organomolybdenum compounds is as follows:
[0024] (1) Add 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence. Slowly heat to 75-85℃ and stir at 100 rpm for 18-24 h. Remove the acetonitrile solvent in a vacuum evaporator, then add 50-100 mL of ethyl acetate. After filtration, a white solid is obtained and washed 3-5 times with a small amount of ethyl acetate. Dry under vacuum at 60-70℃ for 24-48 h to obtain intermediate A.
[0025] (2) Dissolve 0.10-0.11 mol of molybdenum acetylacetonate powder in hot ethanol, and slowly add 0.10-0.12 mol of alcohol solution of intermediate A while stirring. Stir until homogeneous, heat to 75-85℃, reflux for 12-24 h, remove the solvent by vacuum distillation to obtain a dark blue powder, i.e. intermediate B.
[0026] (3) Dissolve 0.10 mol intermediate B and 0.1 mol oleic acid in 50-60 mL of dichloromethane solution, then add 40 mL of 1-2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir the reaction for 8-12 h, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, then wash the product with distilled water until no precipitate is formed in silver nitrate solution, dry the product to obtain organomolybdenum compound;
[0027] The method for preparing graphene grafts is as follows: Anhydrous toluene is placed in a flask, and 0.24-0.53 g of hydroxylated graphene, 12 g of 4-vinylepoxycyclohexane, and 0.1-0.7 g of stannous octoate catalyst are added sequentially. The mixture is ultrasonically treated for 15-30 min at pH 7.5 to ensure uniform mixing. Under nitrogen protection, the mixture is stirred at 110-120℃ for 16-24 h. The reaction mixture is cooled to room temperature, filtered, and the crude product is dissolved in methanol. The solution is then added to a methanol solution containing a small amount of concentrated hydrochloric acid to remove tin residues. The mixture is filtered, washed with dichloromethane and methanol respectively, filtered again, and the product is dried under vacuum to obtain the graphene graft.
[0028] The method for preparing the coumarin derivative is as follows:
[0029] (1) Add 2.62 g of glycine methyl ester hydrochloride to a round-bottom flask and add 15-20 mL of deionized water. Adjust the pH to 8.5-9.0 with triethylamine. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 12-24 h. During the reaction, orange suspensions appear in the flask. Filter and wash to obtain an orange solid crude product. Dry in a vacuum drying oven and recrystallize using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin.
[0030] (2) Transfer the 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step into a 250mL three-necked flask, and add 100mL of dilute hydrochloric acid (concentrated hydrochloric acid:water volume ratio 1:2) to the flask. Hydrolyze at room temperature for 30-60min, adjust the pH to 8-9, and a large amount of brown suspension precipitates in the flask. After the flask cools, filter and wash it to obtain a reddish-brown solid. Recrystallize using EtOH:H2O with a volume ratio of 1:3, and dry to obtain the coumarin derivative.
[0031] The positive effects of this invention are as follows:
[0032] (1) This invention is based on the fact that disulfide bonds are dynamic weak covalent bonds and have lower thermal effect response conditions for reversible covalent bonds. Based on the fact that disulfide bonds are easy to break to form sulfur anions or sulfur free radicals, the energy consumption effect is achieved through the recombination process between different sulfur anions or sulfur free radicals or the reversible reaction between disulfide bonds and mercapto groups. By introducing disulfide bonds into waterborne polyurethane, when polyurethane is exposed to sunlight, the disulfide bonds break first to form free sulfur free radicals. Under sunlight, the sulfur free radicals combine with each other to form disulfide bonds again, thereby absorbing the energy of sunlight on the surface of the polyurethane film and achieving the effect of yellowing resistance, thus preparing a polyurethane coating with yellowing resistance.
[0033] (2) The UV absorber UV-320 is introduced into the chain end of polyurethane through chemical grafting. Since the UV absorber itself can absorb UV light energy and then convert it into heat energy that does not pollute the environment, its mechanism of action is that the intramolecular hydrogen bonds, which are in a closed state, reach an excited state when irradiated by ultraviolet light. Through proton transfer, the intramolecular hydrogen bonds are opened, forming an unstable ketone structure and returning to the ground state. At the same time, the light energy is converted into heat energy and released, reducing the influence of ultraviolet light on the system, thereby improving the yellowing resistance.
[0034] (3) The reaction of polyol and isocyanate is used to introduce disulfide compound as chain extender into the prepolymer chain segment of polyurethane. At the same time, UV absorber UV-320 is added to carry out the reaction. The present invention uses the multiple effects of disulfide bond and UV absorber light absorption to improve the yellowing resistance of polyurethane.
[0035] (4) The nitrogen-phosphorus-silicon flame retardant of the present invention is based on ZL2023111285422 of the research group of the first inventor. The preparation principle of the nitrogen-phosphorus-silicon flame retardant is as follows: the phosphorus-hydrogen bond (PH) in DOPO reacts with organic molybdenum compound and graphene graft under the action of azobisisobutyronitrile to introduce a group with smoke suppression. Then, it undergoes an addition reaction with the carbon-carbon double bond (-C=C-) on maleic anhydride to generate an intermediate. DOPO provides carbon source and acid source. Maleic anhydride provides carbon source. The anhydride group in the intermediate undergoes a ring-opening reaction with the NH bond and some hydroxyl groups in diisopropanolamine to generate a new intermediate flame retardant with hydroxyl groups. Diisopropanolamine provides gas source. When the flame retardant is heated and decomposed, on the one hand, ammonia and nitrogen oxides are generated to reduce the weight of the system, and on the other hand, the gas is generated and wrapped on the surface, thereby isolating the air and reducing the contact area with the combustion-supporting gas. On the other hand, the intermediate flame retardant decomposes upon heating, continuously producing acidic substances such as polyphosphoric acid and polymetaphosphoric acid, which promotes surface carbonization and forms a dense, porous carbon layer on its surface, achieving a flame retardant effect. Simultaneously, the intermediate flame retardant containing hydroxyl groups reacts with the C-Cl bonds of TCPP in a weakly alkaline environment. This increases the phosphorus content in the system, providing an additional acid source for carbonization under heating. Furthermore, since the C-Cl content is lower than that of DIPA, some hydroxyl groups still react with the Si-Cl of methyltrichlorosilane to obtain a nitrogen-phosphorus-silicon flame retardant. The introduction of organosilicon compounds into this flame retardant system increases the density of the heated Si-C carbon layer. Introducing this nitrogen-phosphorus-silicon flame retardant into the polyurethane chain reduces the dripping and smoke characteristics of polyurethane combustion.
[0036] (5) Traditional inorganic molybdenum compounds have poor compatibility with polyurethane and will precipitate in less than 2 hours when dispersed in the polyurethane system. 1-bromotetradecane and N-methyldiethanolamine are selected to react to form a quaternary ammonium salt compound with hydroxyl groups. Then, molybdenum acetylacetonate is used to complex with the quaternary ammonium salt compound to introduce the molybdenum compound into the system to form an organic molybdenum compound that is compatible with polyurethane, thereby reducing the amount of smoke released during the combustion of polyurethane.
[0037] (6) In this invention, hydroxylated graphene and 4-vinylepoxycyclohexane are used in an alkaline environment under the action of stannous octoate catalyst. The epoxy group and the hydroxyl group on the graphene ring open, introducing the graphene into the 4-vinylepoxycyclohexane molecular chain. At the same time, new hydroxyl groups are generated. The high char-forming properties of hydroxylated graphene and 4-vinylepoxycyclohexane are utilized to generate a high density carbon layer during the combustion of waterborne polyurethane, reducing the combustion process. At the same time, the 4-vinylepoxy ring is introduced into the polyurethane molecular chain, improving the wear resistance of the polyurethane.
[0038] (7) In this invention, glycine methyl ester hydrochloride is reacted with salicylaldehyde to obtain 3-(2-(hydroxybenzyl)amino)coumarin. The carbon-nitrogen double bond is broken by hydrolysis with dilute hydrochloric acid to form an amino group, so that the obtained coumarin derivative has an amino group. It can react with isocyanate to introduce coumarin functional groups into the polyurethane chain. In this invention, the two coumarin groups will undergo a [2+2] cycloaddition reaction under ultraviolet light irradiation near 365nm to generate a dimer with a cyclobutane structure. The optical activity of the coumarin functional group is relatively high. Under the action of ultraviolet light of different wavelengths, it can carry out reversible photodimerization reaction and photodepolymerization reaction near 254nm. Energy is consumed by continuous polymerization and depolymerization, reducing the yellowing effect on polyurethane. No catalyst needs to be added in the whole reversible process.
[0039] (8) Hydroxypropyl propargyl ether is reacted with isocyanate to introduce hydroxypropyl propargyl ether with bright reflective properties into the polyurethane chain. Glutaric acid enhances the smoothness of the surface of the polyurethane film by hydroxypropyl propargyl ether, thereby forming a smooth surface that can reflect more light and improve the light resistance of polyurethane. This invention uses hydroxypropyl propargyl ether, coumarin derivatives, disulfide compounds and ultraviolet absorbers to improve the light resistance of polyurethane.
[0040] In this invention, "part" is equivalent to "g". Attached Figure Description
[0041] Figure 1 Electron micrograph of a pure water-based polyurethane carbon layer calcined at 500℃;
[0042] Figure 2 Electron micrograph of the polyurethane carbon layer obtained by adding nitrogen, phosphorus and silicon flame retardants at calcination temperature of 500℃. Detailed Implementation
[0043] The present invention will be further described below with reference to the embodiments.
[0044] The chemical materials from unspecified manufacturers involved in the embodiments of this invention can be replaced by similar products from Shanghai Maclean Biochemical Co., Ltd.
[0045] Example 1
[0046] Preparation method of graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coatings.
[0047] (1) Prepolymerization: First, the polytetrahydrofuran ether glycol and polypropylene glycol were vacuum dried for 18 hours; then 20 parts of polytetrahydrofuran ether glycol (molecular weight of 1000 g / mol) and 49 parts of HDI were added to a flask with a thermometer, glass stopper, stirrer and nitrogen tube. Then 0.1 parts of dibutyltin dilaurate were added, the temperature was raised to 80℃, the rotation speed was 200 r / min, and the reaction was carried out for 1 hour. The temperature was adjusted to 75℃, and 10 parts of polyethylene glycol with a molecular weight of 2000 g / mol were added to the reaction system and reacted for 1 hour to obtain the prepolymer.
[0048] (2) First chain extension and introduction of disulfide bonds: Add 2 parts of 1,4-butanediol BDO and 2 parts of 2,2'-dithiodiethanol to the prepolymer and react at 70°C for 1 h. Then add 5 parts of polyethylene glycol monomethyl ether (MPEG, molecular weight 516 g / mol, the same below) to the reaction system and react at 70°C for 1 h. During this period, observe the state of the reactants. If the viscosity increases, add acetone in small amounts several times to reduce the viscosity. Then add 3 parts of UV-320, 0.6 parts of coumarin derivative, 0.3 parts of hydroxypropyl propargyl ether, 3 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid and react at 70°C for 1 h.
[0049] (3) Secondary chain extension: Adjust the rotation speed to 250 r / min, add 1 part of ethylenediamine, stir and react at 60℃ for 0.5 h, add 100 parts of water at 60℃, stir at 2000 r / min, and react at 60℃ for 0.5 h to obtain graphene-type flame retardant, light resistant, and wear resistant water-based polyurethane coating.
[0050] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: Using 100 mL of tetrahydrofuran as solvent, add 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 3.9 g of organomolybdenum compound, 0.6 g of graphene graft, and 0.5 g of azobisisobutyronitrile (AIOBT). React at 50 °C for 1 h. Then add 0.1 mol of maleic anhydride (MA) to a four-necked flask and stir at 40 °C for 4 h. Dry in a vacuum oven to obtain the DOPO-MA reaction system. Further add... 0.12 mol of diisopropanolamine (DIPA) and 0.41 g of p-toluenesulfonic acid (TsOH) were added to a flask, followed by 50 mL of toluene. The mixture was reacted at 90 °C for 3 h and then dried under vacuum at 85 °C to constant weight to obtain an intermediate flame retardant. 0.01 mol of tris(1-chloro-2-propyl) phosphate was then added to the intermediate flame retardant, and the pH was adjusted to 7.5. The mixture was reacted at 75 °C for 1 h, and then the pH was adjusted again to 7.5. 0.01 mol of methyltrichlorosilane was then added, and the mixture was reacted at 80 °C for 1 h and then dried under vacuum to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0051] The preparation method of organomolybdenum compounds is as follows:
[0052] (1) Add 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence. Slowly heat to 75 °C and stir at 100 rpm for 18 h. Remove the acetonitrile solvent in a vacuum evaporator. Add 50 mL of ethyl acetate and filter to obtain a white solid. Wash with a small amount of ethyl acetate three times and dry under vacuum at 60 °C for 24 h to obtain intermediate A.
[0053] (2) Dissolve 0.10 mol of molybdenum acetylacetonate powder in hot ethanol, and slowly add 0.10 mol of ethanol solution of intermediate A while stirring. After stirring evenly, heat to 75°C and reflux for 12 h. Remove the solvent by vacuum distillation to obtain a dark blue powder, i.e., intermediate B.
[0054] (3) Dissolve 0.10 mol intermediate B and 0.1 mol oleic acid in 50 mL of dichloromethane solution, then add 40 mL of 1 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir the reaction for 8 h, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, then wash the product with distilled water until no precipitate is formed in silver nitrate solution, dry the product to obtain organomolybdenum compound;
[0055] The graphene graft was prepared as follows: 50 mL of anhydrous toluene was placed in a flask, and 0.24 g of hydroxylated graphene, 12 g of 4-vinylepoxycyclohexane, and 0.1 g of stannous octoate catalyst were added sequentially. Under the action of pH 7.5, the mixture was ultrasonically treated for 15 min to make it uniform. Under nitrogen protection, the mixture was stirred at 110 °C for 16 h. The reaction mixture was cooled to room temperature and filtered. The crude product was dissolved in methanol. The solution was then added to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residue. The mixture was filtered and washed with dichloromethane and methanol, respectively. The product was dried under vacuum to obtain the graphene graft.
[0056] The preparation method of coumarin derivatives is as follows:
[0057] (1) Add 2.62 g of glycine methyl ester hydrochloride and 15 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 12 h. During the reaction, orange suspensions appeared in the flask. After filtration and washing, an orange solid crude product was obtained. The product was dried in a vacuum drying oven and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin.
[0058] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed at a volume ratio of 1:2) was added to the flask. Hydrolysis was carried out at room temperature for 30min. The pH was adjusted to 8-9. A large amount of brown suspension was precipitated in the flask. After the flask cooled, it was filtered and washed to obtain a reddish-brown solid. Recrystallization was carried out using EtOH:H2O at a volume ratio of 1:3 to obtain the coumarin derivative.
[0059] Example 2
[0060] Preparation method of graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coatings.
[0061] (1) Prepolymerization: First, polytetrahydrofuran ether glycol and polypropylene glycol were vacuum dried for 24 hours; 25 parts of polypropylene glycol (molecular weight of 2000 g / mol) and 64 parts of MDI were added to a flask with a thermometer, glass stopper, stirrer and nitrogen tube, and 0.3 parts of dibutyltin dilaurate were added. The temperature was raised to 85°C and the rotation speed was 250 r / min. The reaction was carried out for 2 hours; the temperature was adjusted to 80°C and 12 parts of polyethylene glycol with a molecular weight of 2000 g / mol were added to the reaction system and reacted for 2 hours to obtain the prepolymer.
[0062] (2) First chain extension and introduction of disulfide bonds: Add 3 parts of 1,4-butanediol BDO and 3 parts of 2,2-diaminodiphenyl disulfide, react at 80°C for 2 hours, then add 6 parts of polyethylene glycol monomethyl ether (MPEG) to the prepolymer of step (1), react at 70°C for 2 hours. During this period, observe the state of the reactants. If the viscosity increases, add acetone in small amounts several times to reduce the viscosity. Then add 5 parts of UV-531, 1.5 parts of coumarin derivative, 1.2 parts of hydroxypropyl propargyl ether, 5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid, react at 80°C for 1.5 hours.
[0063] (3) Secondary chain extension: Adjust the rotation speed to 300 r / min, add 2 parts of ethylenediamine, stir and react at 70℃ for 1 h, add 120 parts of water at 70℃, keep the stirring speed at 2000 r / min, and react for 1 h to obtain graphene-type flame retardant, light resistant, and wear resistant water-based polyurethane coating.
[0064] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: using 100 mL of tetrahydrofuran as solvent, add 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 6.5 g of organomolybdenum compound, 1 g of graphene graft, and 0.7 g of azobisisobutyronitrile (AIO). React at 60 °C for 2 h, then add 0.12 mol of maleic anhydride (MA) to a four-necked flask, stir and react at 50 °C for 6 h, and dry in a vacuum oven to obtain the DOPO-MA reaction system; then add 0. 14 mol of diisopropanolamine (DIPA) and 0.43 g of p-toluenesulfonic acid (TsOH) were placed in a flask, and 50 mL of toluene was added. The mixture was heated at 100 °C for 6 h and then dried under vacuum at 85 °C to constant weight to obtain an intermediate flame retardant. 0.015 mol of tris(1-chloro-2-propyl) phosphate was then added to the intermediate flame retardant, and the pH was adjusted to 7.5. The mixture was reacted at 85 °C for 2 h, and then the pH was adjusted again to 7.5. 0.015 mol of methyltrichlorosilane was added, and the mixture was reacted at 85 °C for 2 h. The mixture was then dried under vacuum to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0065] The preparation method of organomolybdenum compounds is as follows:
[0066] (1) Add 0.1 mol of 1-bromotetradecane, 0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence. Slowly heat to 85 °C and stir at 100 rpm for 24 h. Remove the acetonitrile solvent in a vacuum evaporator. Add 100 mL of ethyl acetate and filter to obtain a white solid. Wash with a small amount of ethyl acetate 5 times and dry under vacuum at 70 °C for 48 h to obtain intermediate A.
[0067] (2) Dissolve 0.11 mol of molybdenum acetylacetonate powder in hot ethanol, and slowly add 0.12 mol of alcohol solution of intermediate A while stirring. After stirring evenly, heat to 85°C and reflux for 24 h. Remove the solvent by vacuum distillation to obtain a dark blue powder, i.e., intermediate B.
[0068] (3) Dissolve 0.10 mol intermediate B and 0.1 mol oleic acid in 60 mL of dichloromethane solution, then add 40 mL of 2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir the reaction for 12 h, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, then wash the product with distilled water until no precipitate is formed in silver nitrate solution, dry the product to obtain organomolybdenum compound;
[0069] The method for preparing the graphene graft is as follows: 50 mL of anhydrous toluene is placed in a flask, and 0.53 g of hydroxylated graphene, 12 g of 4-vinylepoxycyclohexane and 0.7 g of stannous octoate catalyst are added sequentially. Under the action of pH 7.5, the mixture is ultrasonically treated for 30 min to make it uniform. Under nitrogen protection, the mixture is stirred at 120 °C for 24 h. The reaction mixture is cooled to room temperature, filtered, and the crude product is dissolved in methanol. The solution is then added to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residue. The mixture is filtered, washed with dichloromethane and methanol respectively, filtered, and the product is dried under vacuum to obtain the graphene graft.
[0070] The method for preparing the coumarin derivative is as follows:
[0071] (1) Add 2.62 g of glycine methyl ester hydrochloride and 20 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 24 h. During the reaction, orange suspensions appeared in the flask. After filtration and washing, an orange solid crude product was obtained. The product was dried in a vacuum drying oven and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzyl)amino)coumarin.
[0072] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed at a volume ratio of 1:2) was added to the flask. Hydrolysis was carried out at room temperature for 60min. The pH was adjusted to 8-9. A large amount of brown suspension was precipitated in the flask. After the flask cooled, it was filtered and washed to obtain a reddish-brown solid. Recrystallization was carried out using EtOH:H2O at a volume ratio of 1:3 to obtain the coumarin derivative.
[0073] Example 3
[0074] Preparation method of graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coatings.
[0075] (1) Prepolymerization: First, polytetrahydrofuran ether glycol and polypropylene glycol were vacuum dried for 21 h; then 22.5 parts of polytetrahydrofuran ether glycol (molecular weight of 1000 g / mol) and 56.5 parts of MDI were added to a flask with a thermometer, glass stopper, stirrer and nitrogen tube. Then 0.2 parts of dibutyltin dilaurate were added, the temperature was raised to 80℃, the rotation speed was 225 r / min, and the reaction was carried out for 1.5 h; the temperature was adjusted to 80℃, and 11 parts of polyethylene glycol with a molecular weight of 2000 g / mol were added to the reaction system and reacted for 1.5 h to obtain the prepolymer.
[0076] (2) First chain extension and introduction of disulfide bonds: 2.5 parts of 1,4-butanediol BDO and 2.5 parts of 2,2'-dithiodiethanol were added to the prepolymer system and reacted at 75°C for 1.5 h. Then, 5.5 parts of polyethylene glycol monomethyl ether (MPEG) were added to the reaction system and reacted at 70°C for 1.5 h. During this period, the state of the reactants was observed at all times. If the viscosity increased, acetone was added in small amounts and multiple times to reduce the viscosity. Then, 4 parts of UV absorber UV-320, 1 part of coumarin derivative, 0.75 parts of hydroxypropyl propargyl ether, 4 parts of nitrogen and phosphorus flame retardant and 0.01 parts of glutaric acid were added and reacted at 75°C for 1 h.
[0077] (3) Secondary chain extension: Adjust the rotation speed to 275 r / min and add 1.5 parts of ethylenediamine. Stir and react at 65℃ for 0.5 h. Add 110 parts of water at 65℃ and keep the stirring speed at 2000 r / min. React for 1 h to obtain graphene-type flame retardant, light resistant, and wear resistant water-based polyurethane coating.
[0078] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: Using 100 mL of tetrahydrofuran as solvent, add 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 5.2 g of organomolybdenum compound, 0.8 g of graphene graft, and 0.6 g of azobisisobutyronitrile (AIO). React at 55 °C for 1.5 h. Then add 0.11 mol of maleic anhydride (MA) to a four-necked flask, stir the reaction at 45 °C for 5 h, and dry in a vacuum oven to obtain the DOPO-MA reaction system. Then add... 0.13 mol of diisopropanolamine (DIPA) and 0.42 g of p-toluenesulfonic acid (TsOH) were placed in a flask, and 50 mL of toluene was added. The mixture was reacted at 95 °C for 4.5 h, and then dried under vacuum at 85 °C to constant weight to obtain an intermediate flame retardant. 0.01 mol of tris(1-chloro-2-propyl) phosphate was then added to the intermediate flame retardant, and the pH was adjusted to 7.5. The mixture was reacted at 80 °C for 1.5 h, and then the pH was adjusted again to 7.5. 0.0125 mol of methyltrichlorosilane was added, and the mixture was reacted at 80 °C for 1.5 h. The mixture was then dried under vacuum to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0079] The preparation method of organomolybdenum compounds is as follows:
[0080] (1) Add 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence. Slowly heat to 80 °C and stir at 100 rpm for 21 h. Remove the acetonitrile solvent in a vacuum evaporator. Add 75 mL of ethyl acetate and filter to obtain a white solid. Wash with a small amount of ethyl acetate 4 times and dry under vacuum at 65 °C for 36 h to obtain intermediate A.
[0081] (2) Dissolve 0.10 mol of molybdenum acetylacetonate powder in hot ethanol, and slowly add 0.11 mol of alcohol solution of intermediate A while stirring. After stirring evenly, heat to 80°C and reflux for 18 h. Remove the solvent by vacuum distillation to obtain a dark blue powder, i.e. intermediate B.
[0082] (3) Dissolve 0.10 mol intermediate B and 0.1 mol oleic acid in 55 mL of dichloromethane solution, then add 40 mL of 1.5 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir the reaction for 10 h, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, then wash the product with distilled water until no precipitate is formed in silver nitrate solution, dry the product to obtain organomolybdenum compound;
[0083] The method for preparing the graphene graft is as follows: 50 mL of anhydrous toluene is placed in a flask, and 0.38 g of hydroxylated graphene, 12 g of 4-vinylepoxycyclohexane and 0.3 g of stannous octoate catalyst are added sequentially. The mixture is ultrasonically treated for 15 min at pH 7.5 to ensure uniform mixing. The mixture is stirred at 115 °C for 20 h under nitrogen protection. The reaction mixture is cooled to room temperature and filtered. The crude product is dissolved in methanol. The solution is then added to a methanol solution containing a small amount of concentrated hydrochloric acid to remove tin residue. The mixture is filtered and washed with dichloromethane and methanol, respectively. The product is dried as a graphene graft under vacuum.
[0084] The method for preparing the coumarin derivative is as follows:
[0085] (1) Add 2.62 g of glycine methyl ester hydrochloride and 15 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 18 h. During the reaction, orange suspensions appeared in the flask. After filtration and washing, an orange solid crude product was obtained. The product was dried in a vacuum drying oven and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin.
[0086] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed at a volume ratio of 1:2) was added to the flask. Hydrolysis was carried out at room temperature for 45min. The pH was adjusted to 8-9. A large amount of brown suspension was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid. Recrystallization was carried out using EtOH:H2O at a volume ratio of 1:3 to obtain the coumarin derivative.
[0087] Preparation of polyurethane film: The prepared graphene-type flame retardant, light resistant, wear resistant and water-consuming polyurethane coating was poured into a polytetrafluoroethylene mold, the thickness was controlled at 3 mm, and tests such as droplet test, cone calorimetry, and light resistance were carried out.
[0088] The following is the droplet test:
[0089] (1) Sample preparation: Place the prepared PU film in a constant temperature and humidity chamber set at 23℃±0.5℃ and 50%±5% for 48h. Then take it out and cut it into 110cm×10cm×3mm samples. Prepare 2 sets of samples, with 5 samples in each set.
[0090] (2) Setting parameters: Clamp the sample about 5mm from the top so that it is vertically downward. Place a rosin board at the bottom of the sample and pad it with about 0.3g of degreased cotton. Place the sample evenly on the board. Adjust the gas flow rate to 105±5mL / min so that the flame height reaches 20±1mm. Set the ignition time to 10s.
[0091] (3) Flame recording: After setting the parameters, start the flame ignition. After 10 seconds of ignition, press the afterflame time start button. When the sample has finished burning and only sparks remain, press the afterflame combustion end button to enter the afterburn time. When the sample is completely extinguished, press the afterburn time end button to record the afterflame time and afterburn time.
[0092] (4) Observation of molten droplets: During the combustion process, observe whether molten droplets are produced during combustion, and whether the molten droplets falling onto the degreased cotton below will cause secondary combustion. Record the observation results.
[0093] The analysis was performed using ASTM E1354-1990 (2004 standard) and an FTT cone calorimeter 2000 (UK). The sample size was 10 cm × 10 cm, with a thickness of 3 mm, and the thermal radiation power was 12 kW / m². 2 The maximum heat release rate (kW / m) of pkHHR was determined. 2 Total heat released by THR (MJ / m³) 2 pSPR smoke generation rate reaches peak m 2 / s and peak total smoke release (TSR) m 2 / m 2 .
[0094] Yellowing resistance was determined by observing the color change after being exposed to a UV lamp under simulated sunlight for 48 hours. The test was conducted using a bulb-type yellowing resistance instrument, model HZ-3017.
[0095] Reflectance measurement method: The emissivity level of the resin was measured using a Gretag Macbeth Coloreye spectrophotometer (D65 light source, 10-degree observer, including UV) from 360 nm to 750 nm, wherein the maximum emissivity was defined at 660 nm in the present invention.
[0096] The reference document used is Example 3 of 2023111285422.
[0097] Take a test sample with a thickness of 0.1 cm, and test its abrasion resistance according to GB / T22374-2018, 50g / 100r, 50 cycles.
[0098] Table 1 Film-forming properties of polyurethane
[0099]
[0100] The flame retardancy (combustion dripping phenomenon), pkHHR, THR, SPR smoke generation rate and TSR of the polyurethane film in Table 1 are significantly improved compared with the comparative document (Example 3 of 2023111285422); the lightfastness index, which is a measure of yellowing resistance, has increased from 3.5 to 4.0, the reflectivity has increased to over 98%, the wear quality has decreased, and the wear resistance has been significantly improved.
[0101] Table 2 shows the changes in flame retardancy of the unadded materials (based on Example 1).
[0102]
[0103]
[0104] Table 2 shows that combustion without graphene grafts produced molten droplets, while combustion without nitrogen, phosphorus, silicon flame retardants and organic molybdenum compounds increased the pkHHR, TSR, and pSPR smoke generation rates, indicating that these substances played a significant role in flame retardancy.
[0105] Table 3. Changes in lightfastness of the untreated portion of the material (based on Example 1).
[0106]
[0107] Table 3 shows that the yellowing resistance decreased without the addition of coumarin derivatives, salicylaldehyde, hydroxypropyl propargyl ether, 2,2'-dithiodiethanol, and UV-320, indicating that the above materials exhibited good lightfastness. In Example 1, the abrasion resistance without the addition of 4-vinylepoxy ring was 0.0098, while the emulsion with the addition of 2,2'-dithiodiethanol and UV-320 did not show any precipitation, indicating that it did not affect the emulsion stability.
[0108] Using Example 1 as a blank control, UV-Vis spectroscopy revealed that the blank control only had an absorption peak at 230 nm, while the control with added disulfide showed an additional absorption peak at 400 nm. The control with both UV absorber and disulfide showed significantly more absorption at higher wavelengths (450 nm, 550 nm, and 650 nm) compared to the blank control. This indicates that the UV absorber and disulfide have segmented absorption of light. Therefore, theoretically, polyurethane emulsions with added disulfide bonds and UV absorbers have a certain degree of resistance to yellowing. This conclusion can also be drawn from the color difference data.
[0109] Figure 1 and Figure 2 Electron microscopy (EMS) was performed on the carbon layers formed when pure polyurethane and flame-retardant waterborne polyurethane with nitrogen, phosphorus, and silicon flame retardants added during the chain extension stage were calcined in a muffle furnace to 500°C. Observation of the samples at 1600x magnification under an EMS revealed that, compared to pure waterborne polyurethane, the carbon layer of the waterborne polyurethane with added flame retardants was denser and structurally more complete. This indicates that the nitrogen, phosphorus, and silicon groups in the flame retardants exert a synergistic effect, forming a dense and firm carbon layer on the surface of the polyurethane. This effectively prevents oxygen and other combustion-promoting gases from entering the interior of the polyurethane, thus achieving a flame-retardant effect.
Claims
1. A graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coating, characterized in that: The raw materials used include nitrogen, phosphorus, and silicon flame retardants, disulfide compounds, ultraviolet absorbers, organomolybdenum compounds, graphene grafts, and coumarin derivatives; The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: Using 100 mL of tetrahydrofuran as solvent, add 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 3.9-6.5 g of organomolybdenum compound, 0.6-1 g of graphene graft, and 0.5-0.7 g of azobisisobutyronitrile (AIOBR). React at 50-60 °C for 1-2 h. Then add 0.1-0.12 mol of maleic anhydride to a four-necked flask and stir at 40-50 °C for 4-6 h. Dry in a vacuum oven to obtain the DOPO-MA reaction system. Add 0.12-0.14 mol of diisopropanolamine (DIPA) and 0.41-0.43 g of p-toluenesulfonic acid to the system, add 50 mL of toluene, and react at 90-100 °C for 3-6 h. [The final step is to add 85% of the solution to the DOPO-MA reaction system.] The intermediate flame retardant was obtained by vacuum drying at ℃ to constant weight. Then, 0.01~0.015 mol of tris(1-chloro-2-propyl) phosphate was added to the intermediate flame retardant and the pH was adjusted to 7.
5. The reaction was carried out at 75~85 ℃ for 1~2 h. The pH was then adjusted to 7.5, and 0.01~0.015 mol of methyltrichlorosilane was added. The reaction was carried out at 80~85 ℃ for 1~2 h. The mixture was then vacuum dried to constant weight to obtain the nitrogen-phosphorus-silicon flame retardant. The disulfide compound is 2,2'-dithiodiethanol or 2,2-diaminodiphenyl disulfide; The ultraviolet absorber is ultraviolet absorber UV-320 or ultraviolet absorber UV-531; The preparation method of organomolybdenum compounds is as follows: (1) Add 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence. Slowly heat to 75-85℃ and stir at 100 rpm for 18-24 h. Remove the acetonitrile solvent in a vacuum evaporator, then add 50-100 mL of ethyl acetate. After filtration, a white solid is obtained and washed 3-5 times with a small amount of ethyl acetate. Dry under vacuum at 60-70℃ for 24-48 h to obtain intermediate A. (2) Dissolve 0.10~0.11 mol of molybdenum acetylacetonate powder in hot ethanol, and slowly add 0.10~0.12 mol of intermediate A in ethanol solution while stirring. After stirring evenly, heat to 75~85℃ and reflux for 12~24 h. Remove the solvent by vacuum distillation to obtain a dark blue powder, i.e. intermediate B. (3) Dissolve 0.10 mol intermediate B and 0.1 mol oleic acid in 50-60 mL of dichloromethane solution, then add 40 mL of 1-2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir the reaction for 8-12 h, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, then wash the product with distilled water until no precipitate is formed in silver nitrate solution, dry the product to obtain organomolybdenum compound; The method for preparing graphene grafts is as follows: Take 50 mL of anhydrous toluene in a flask, add 0.24~0.53 g of hydroxylated graphene, 12 g of 4-vinylepoxycyclohexane, and 0.1~0.7 g of stannous octoate catalyst in sequence, set the pH to 7.5, and sonicate for 15~30 min to mix evenly. Under nitrogen protection, stir the reaction at 110~120℃ for 16~24 h. Cool the reaction mixture to room temperature, filter, dissolve the crude product in methanol, add the solution to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residue, filter, wash with dichloromethane and methanol respectively, filter, and obtain the dried graphene graft under vacuum conditions. The preparation method of coumarin derivatives is as follows: (1) Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Then add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 12-24 h. During the reaction, orange suspensions appear in the flask. Filter and wash to obtain an orange solid crude product. Dry it in a vacuum drying oven and recrystallize it using the DMF-H2O system to obtain 3-(2-(hydroxybenzyl)amino)coumarin. (2) Transfer the 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step into a 250mL three-necked flask, and add 100mL of dilute hydrochloric acid mixed with concentrated hydrochloric acid and water at a volume ratio of 1:2 to the flask. Hydrolyze at room temperature for 30-60min, adjust the pH to 8-9, and a large amount of brown suspension precipitates in the flask. After the flask cools, filter and wash it to obtain a reddish-brown solid. Recrystallize using EtOH:H2O at a volume ratio of 1:3 to obtain the coumarin derivative. The preparation method of graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coatings is as follows: (1) Prepolymerization: First, the polyol is vacuum dried for 18-24 hours. The polyol is polytetrahydrofuran ether glycol or polypropylene glycol. Then, 20-25 parts of polyol and 49-64 parts of isocyanate are added to a flask with a thermometer, glass stopper, stirrer and nitrogen tube inserted. 0.1-0.3 parts of dibutyltin dilaurate are added. The temperature is raised to 80-85℃ and the rotation speed is 200-250 r / min. The reaction is carried out for 1-2 hours. The temperature is adjusted to 75-80℃. 10-12 parts of polyethylene glycol with a molecular weight of 2000 g / mol are added to the system and reacted for 1-2 hours to obtain the prepolymer. (2) First chain extension and introduction of disulfide bonds: Add 2-3 parts of 1,4-butanediol BDO and 2-3 parts of disulfide compound to the prepolymer, react at 70-80℃ for 1-2 hours, then add 5-6 parts of polyethylene glycol monomethyl ether, react at 70℃ for 1-2 hours. During this period, observe the state of the reactants. If the viscosity increases, add acetone in small amounts multiple times to reduce the viscosity. Then add 3-5 parts of ultraviolet absorber, 0.6-1.5 parts of coumarin derivative, 0.3-1.2 parts of hydroxypropyl propargyl ether, 3-5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid, react at 70-80℃ for 1-1.5 hours. (3) Secondary chain extension: Adjust the rotation speed to 250~300 r / min, add 1~2 parts of ethylenediamine, stir and react at 60~70℃ for 0.5~1h, add 100~120 parts of water, keep the stirring speed at 2000 r / min at 60~70℃, and react for 0.5~1h to obtain graphene-type flame retardant, light resistant, and wear resistant water-based polyurethane coating.
2. The graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coating as described in claim 1, characterized in that, The molecular weight of polytetrahydrofuran ether diol is 1000 g / mol, and the molecular weight of polypropylene glycol is 2000 g / mol.
3. The graphene-based flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coating as described in claim 1, characterized in that... The isocyanate can be either HDI or MDI.
Citation Information
Patent Citations
Preparation and application method of self-repairing flame-retardant molten-drop-resistant wear-resistant polyurethane coating
CN113956777A
Preparation method of matte waterborne polyurethane emulsion with flame-retardant and self-repairing functions and flame-retardant coating
CN115819704A